Food Crop and Klanceng Bee Cultivation Development in Supporting the Food Security Tourism Development in Srimulyo Village: Pengembangan Budidaya Tanaman Pangan dan Lebah Klanceng Dalam Mendukung Pengembangan Wisata Ketahanan Pangan Desa Srimulyo - Chatarina Lilis Suryani; Siti Tamaroh; Prabu Ariawangningrati; Hilma Amanda Ansabila; FX Suwarta (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Srimulyo Village began to be developed into a Food Security Tourism Village, since 2023. The problems faced by the people of Srimulyo Village, especially Dusun Payak Cilik, are the low level of community involvement and the benefits obtained from tourism development are still low. Around Srimulyo Village, there are many flowers that are a source of bee food, so that klanceng bee cultivation has great potential to be developed. In addition, there are also many empty lands along the banks of the Opak River that have the potential for developing food crops. Solutions to the problem are directed at increasing knowledge of how to cultivate food crops, diversifying processed products, klanceng bee cultivation that can be integrated with the development of tourist villages, improving organizational management, and increasing financial literacy. The stages of activity include preparation and coordination, counseling and practice of food crop cultivation, processing tubers, counseling and practice of klanceng cultivation, counseling on organizational management and financial literacy, as well as evaluation and monitoring. The activity began with the stage of socialization and coordination of activities with the CUCT cooperative management and the Dwi Manunggal Farmers Group. The activity was attended by 20 members of the farmer group. Based on the questionnaire given, it is known that the understanding of farmer group members about food crop cultivation, product processing, and how to cultivate klanceng bees is still low (only 15%). After the extension, it increased to 85%.